Time Utilization Pattern among Hill Women - Saikia, R. (Indian Journal of Hill Farming, 2018)
The present study was carried out in Karbi Anglong district of Assam, considering the women folk of the Karbi tribe. The socio-economic profile of the respondents showed that majority of the respondents belongs to the age group of 30-40 yrs of age and higher percentage of the respondents is found to be illiterate. Nuclear family is more prevalent and having large family size. Majority of the respondents resides in kutcha (mud floor and thatched) house and belongs to poor economic group. Observation showed that all the respondents performed almost all the activities while working towards upliftment the family. Time utilization pattern reveals that the majority of the respondents spent 11–13 h in home and allied activities during non-agricultural season and 7–9hrs during agricultural season and spend 5 -7 h in farm activities during agricultural season. Thus, it can be divulged that respondents engage themselves in economic activities from dawn to dusk in order to uplift their financial status to meet the family needs.